Prostate cancer knowledge and screening practices among men from Tharaka Nithi County, Kenya - Mwangi, Joshua K.; Agina, Bonaventure O.; Mwanzo, Isaac (International Journal Of Community Medicine And Public Health, 2025)
Background: Prostate cancer (PCa) is the second most commonly diagnosed cancer and the fifth leading cause of cancer death among men. In Kenya it is the leading male cancer (21.9%) followed by colorectal cancer (8,3%). It is amenable if detected early. Knowledge on prostate cancer and its screening practices are some of the predictors associated with early diagnosis and treatment. The purpose of this study was to determine PCa knowledge levels and screening practices among men from Tharaka Nithi County in Kenya. Methods: Cross-sectional study design was adopted and multi-stage sampling was used eventually recruiting 382 men who were 40 years old and above. Researcher administered questionnaires were used to collect data. Data analysis was done using the statistical package of social science (SPSS) version 22. Results: Awareness level of prostate cancer was high (85.1%) among participants. Majority of the participants (69.1%) had poor knowledge and screening levels were low (4.5%). Factors found to be significantly associated with PCa knowledge were prostate cancer awareness (p=0.022), awareness on PCa screening tests (p<0.001) and family history of PCa (p<0.001), while those found to be significantly associated with screening were level of education (p=0.001), awareness of PCa screening tests (p<0.001), family history of PCa (p=0.012) and knowledge on PCa (p=0.044). Conclusions: Knowledge on PCa and PCa screening services were low among men in Tharaka Nithi County and therefore there is need for the County government to come up with strategies aimed at increasing the level of knowledge on PCa and scaling up of PCa screening services.